1989
DOI: 10.1007/bf00413136
|View full text |Cite
|
Sign up to set email alerts
|

Transport of branched-chain amino acids in Corynebacterium glutamicum

Abstract: The transport of branched-chain amino acids was characterized in intact cells of Corynebacterium glutamicum ATCC 13032. Uptake and accumulation of these amino acids occur via a common specific carrier with slightly different affinities for each substrate (Km[Ile] = 5.4 microM, Km[Leu] = 9.0 microM, Km[Val] = 9.5 microM). The maximal uptake rates for all three substrates were very similar (0.94 - 1.30 nmol/mg dw.min). The optimum of amino acid uptake was at pH 8.5 and the activation energy was determined to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…For most experiments a complex medium (BHI) consisting of 37 g of brain heart infusion (DIFCO) per liter (pH 7.5) was used. Where indicated, cells were grown in the following minimal medium (MMI) with glucose as the carbon source (25 g/liter): (NH4)2SO4, 5 g/liter; urea, 5 g/liter; KH2PO4, 2 g/liter; K2HPO4, 2 g/liter; MgSO4 * 7H20, 250 mg/liter; FeSO4 * 7H20, 10 mg/liter; CaCl2 * 2H20, 10 mg/liter; MnSO4 1H20, 10 mg/ liter; and trace amounts of ZnSO4, H3B03, CoC12, CuS04, NiCl, and NaMoO4 (pH 7.0) (7,8). Cell mass was determined by measuring the optical density at 600 nm, with a value of 1 corresponding to 0.32 mg (dry mass)/ml.…”
Section: Materuils and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For most experiments a complex medium (BHI) consisting of 37 g of brain heart infusion (DIFCO) per liter (pH 7.5) was used. Where indicated, cells were grown in the following minimal medium (MMI) with glucose as the carbon source (25 g/liter): (NH4)2SO4, 5 g/liter; urea, 5 g/liter; KH2PO4, 2 g/liter; K2HPO4, 2 g/liter; MgSO4 * 7H20, 250 mg/liter; FeSO4 * 7H20, 10 mg/liter; CaCl2 * 2H20, 10 mg/liter; MnSO4 1H20, 10 mg/ liter; and trace amounts of ZnSO4, H3B03, CoC12, CuS04, NiCl, and NaMoO4 (pH 7.0) (7,8). Cell mass was determined by measuring the optical density at 600 nm, with a value of 1 corresponding to 0.32 mg (dry mass)/ml.…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…On the other hand, isoleucine clearly differs from lysine with respect to hydrophobicity and thus to the ability to cross the membrane by diffusion. Furthermore, the uptake systems for lysine and isoleucine are completely different, i.e., an antiport mechanism with extremely low activity for the former and a Na+-coupled symport mechanism for the latter (2,7). The mechanism of excretion in the case of glutamate is fundamen-tally different from those responsible for lysine and isoleucine (11).…”
mentioning
confidence: 99%
“…Whereas a considerable amount of data exist concerning the physiology of these bacteria, especially under conditions of amino acid overproduction (18), very little information is available concerning transport processes in corynebacteria (2,17,24). Recently we have published studies about uptake and excretion of isoleucine (8,9) and glutamate in these bacteria and possible interactions between import and export (11,12).…”
mentioning
confidence: 99%
“…Using a variety of techniques, such as transcript profiling, proteome analysis, and enzymatic studies, we could finally ascribe the inhibitory effect of valine on the isoleucineauxotrophic VAL1 strain to a competition of isoleucine with valine for uptake by BrnQ. This secondary carrier is responsible for the uptake of all branched-chain amino acids in C. glutamicum (52) and has only slightly different affinities for them (15). The isoleucine transport inhibition could be autoamplified by decreased BrnQ levels, since it has been reported that brnQ is expressed only if the internal isoleucine concentration exceeds 0.5 mM (5).…”
Section: Discussionmentioning
confidence: 99%
“…From the sum of the results described above, the conclusion was drawn that the isoleucine limitation in the presence of valine or leucine is caused by the competition of these amino acids with isoleucine uptake by the carrier protein BrnQ (15,52). This carrier is responsible for the uptake of all three branched-chain amino acids, and therefore, high concentrations of valine or leucine compete for the uptake of the essential supplement isoleucine, which usually was present at an initial concentration of 3.4 mM in the medium.…”
Section: Ncgl1222mentioning
confidence: 99%